Bottom-up Analysis of Cases of Collaboration and Integration in Maritime Tourism Policy Domains in South Sulawesi - Safira Nadhila Firdhausa; Seniwati Seniwati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research examines the bottom-up approach to maritime tourism policy in South Sulawesi, primarily focusing on collaboration and policy integration. This method involves the local community as the primary stakeholder who can determine the potential and needs of maritime tourism in their area. Data was collected through interviews with the South Sulawesi Provincial Culture and Tourism Office and analysis of relevant documents. The research results indicate that policy collaboration is carried out through cooperation between the government, namely the South Sulawesi Provincial Culture and Tourism Office, local actors, and the private sector. Furthermore, integrating inter-sectoral policies ensures that the development of tourism proceeds synergistically by considering several aspects, such as economic, social, and environmental factors. The bottom-up approach also supports the sustainability of maritime tourism through several empowerment initiatives for local communities. They should also be involved in the management of maritime tourism destinations and the promotion of local products. It can be concluded that a bottom-up approach involving inter-sectoral cooperation and policy integration encourages the development of sustainable maritime tourism while still paying attention to several aspects, such as local economic empowerment, social welfare, and environmental preservation.